Reconstruction of Moon Phases and Period in The Book of Enoch on Islamic Astronomy Perspective - Azkarrula, Youla Afifah; Anam, Ahmad Syifaul (Asy-Syari'ah, 2024)
Abstract: The Book of Enoch presents an explanation of Moon in a different way when compared to many ancient manuscripts. The periods of the Moon associated with the Moon phases are illustrated in a unique way that, in first glance, requires a deep understanding. This explanation is different with what science has explained nowadays. To begin with, the previous research of this subject on the Book of Enoch is out to dated. Therefore, this research conducts a new approach to examine the Book of Enoch using Islamic perspective where this study is rare to conduct. This study utilizes qualitative research with content analysis to gain the answer in depth. This research also uses triangulation method to investigate the data and obtain the validity of the results. Overall, the Moon phase in the Book of Enoch has the same understanding as the modern science. The Book of Enoch describes implicitly the appearance of Moon in the northern hemisphere. The explanation of Enoch lunar-day in each month is followed by the Urfi Islamic calendar. Then the statement about “once the month is 28-day” is based on the using of Callippic cycle in Charles opinion while in the author’s opinion that the Book of Enoch shows the sidereal month cycle. In addition, the theory which has been adopted by Islamic astronomy has a strong relationship with this manuscript since it is believed that this manuscript is attributed to Prophet Enoch or Idris. Abstrak: Kitab Henokh menyajikan penjelasan tentang Bulan dengan cara yang berbeda jika dibandingkan dengan banyak naskah kuno. Periode Bulan yang terkait dengan fase Bulan diilustrasikan dengan cara yang unik sehingga sekilas memerlukan pemahaman yang mendalam. Penjelasan ini berbeda dengan penjelasan ilmu pengetahuan saat ini. Pertama-tama, penelitian sebelumnya mengenai subjek Kitab Henokh ini sudah ketinggalan zaman. Oleh karena itu, penelitian ini melakukan pendekatan baru untuk mengkaji Kitab Henokh dengan menggunakan perspektif Islam dimana penelitian ini jarang dilakukan. Penelitian ini menggunakan penelitian kualitatif dengan analisis isi untuk memperoleh jawaban secara mendalam. Penelitian ini juga menggunakan metode triangulasi untuk menyelidiki data dan memperoleh keabsahan hasil. Secara keseluruhan, fase Bulan dalam Kitab Henokh mempunyai pemahaman yang sama dengan ilmu pengetahuan modern. Kitab Henokh menggambarkan secara implisit penampakan Bulan di belahan bumi utara. Penjelasan hari lunar Henokh di setiap bulannya diikuti dengan penanggalan Islam Urfi. Kemudian pernyataan “satu bulan ada 28 hari” didasarkan pada penggunaan siklus Callippic menurut pendapat Charles sedangkan menurut pendapat penulis Kitab Henokh menunjukkan siklus bulan sidereal. Selain itu, teori yang dianut oleh ilmu astronomi Islam mempunyai kaitan erat dengan naskah ini karena diyakini naskah ini milik Nabi Henokh atau Idris.